High-ductility fiber reinforced concrete integrated molding method
Patent Information
- Application Number
- CN202611404555.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种高韧性纤维增强混凝土一体化成型方法,解决了上述背景技术中提出的混凝土盖板的韧性和抗裂性能受限,影响盖板的使用安全性的问题
1.本发明中,通过将聚乙烯醇纤维与玄武岩纤维按特定质量比混合,并加入纤维素醚分散剂进行干混,得到混杂纤维混合物,提高了纤维在混凝土基体中的分散均匀性;在纤维与基体复合搅拌过程中通过冷却水循环系统控制温度,并加入聚丙烯腈纤维,增强了纤维与基体的粘结性能,从而提升了混凝土盖板的整体韧性和抗裂性能。
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to an integrated molding method for high-toughness fiber-reinforced concrete. Background Technology
[0002] Concrete covers are a commonly used precast cement component, mainly used to cover cable trenches, drainage ditches, or inspection wells. They can protect underground pipelines and withstand vehicle and pedestrian loads. They have advantages such as low cost, high production efficiency, and high flexibility. They are widely used in bridge construction, cable trench construction, drainage ditch construction, and high-rise building construction.
[0003] Currently, in the preparation process of unreinforced ultra-tough concrete cover plates, existing technologies generally suffer from poor dispersion of fiber materials in the matrix. Traditional reinforced concrete cover plates have defects such as large thickness, heavy weight, and easy corrosion of reinforcing bars, making it difficult to achieve uniform mixing and stable bonding of various fibers. This results in limited toughness and crack resistance of the concrete cover plate, affecting the safety of its use.
[0004] Therefore, a method for integral molding of high-toughness fiber-reinforced concrete is proposed to solve the above problems. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides an integrated molding method for high-toughness fiber-reinforced concrete, which solves the problem mentioned in the background art of limited toughness and crack resistance of concrete cover plates, affecting the safety of cover plate use.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for integral molding of high-toughness fiber-reinforced concrete, comprising the following steps: Step 1: Fiber dispersion pretreatment. Polyvinyl alcohol fibers with a length of 6-12 mm and basalt fibers with a length of 8-15 mm are mixed at a mass ratio of 1:0.5 to 1:2. 0.5%-2% of cellulose ether dispersant by the total mass of the fibers is added. The mixture is then dry-mixed in a mixer at a speed of 200-400 rpm for 3-5 minutes to obtain a mixed fiber mixture. Step 2: Preparation of matrix slurry. Cement, silica fume, quartz sand, naphthalene-based high-efficiency water-reducing agent and water are mixed at a mass ratio of 1:0.15-0.3:0.8-1.5:0.01-0.03:0.25-0.35 and stirred in a mixer at a speed of 600-1000 rpm for 5-10 minutes to obtain a concrete matrix slurry with a fluidity of 180-220 mm. Step 3: Composite mixing of fiber and matrix. Slowly add the mixed fiber mixture to the concrete matrix slurry and continue mixing at 400-600 rpm for 3-8 minutes to obtain unreinforced ultra-tough concrete mixture. Step 4: Compression molding. The unreinforced ultra-tough concrete mixture is injected into the mold and vibrated to compact it for 2-5 minutes under the conditions of vibration frequency of 50-100Hz and amplitude of 0.5-1.5mm. Then, it is compression molded to obtain the cover plate blank. Step 5: Integrated curing. Place the cover plate blank along with the mold in a curing room with a temperature of 20-30℃ and a relative humidity of over 95% for 12-24 hours. After demolding, place the cover plate in a steam curing chamber with a temperature of 80-95℃ for 8-16 hours, and then transfer it to an indoor environment with a temperature of 20-25℃ for natural curing for 3-7 days to obtain a high-toughness fiber-reinforced concrete cover plate.
[0007] Preferably, in step one, the diameter of the polyvinyl alcohol fiber is 10-30 μm, the diameter of the basalt fiber is 12-20 μm, and the total volume content of the polyvinyl alcohol fiber and basalt fiber in the mixed fiber mixture is 1.5%-3.5% of the total volume of the concrete.
[0008] Preferably, in step one, before the fiber dispersion pretreatment, the polyvinyl alcohol fiber and basalt fiber are respectively placed in an oven at a temperature of 60-80℃ for 1-2 hours for drying. The dried fibers are premixed in a mixer at 100-200 rpm for 2-3 minutes, and then a cellulose ether dispersant, hydroxypropyl methylcellulose, is added for dry mixing.
[0009] Preferably, in step two, the cement is 52.5 grade ordinary Portland cement with a specific surface area ≥350m² / kg; The silica fume has a SiO2 content of ≥92% and a specific surface area of ≥18000 m² / kg; The particle size range of quartz sand is 0.1-1.0 mm, of which 0.1-0.3 mm particles account for 30%-40%, 0.3-0.6 mm particles account for 40%-50%, and 0.6-1.0 mm particles account for 10%-30%. The naphthalene-based high-efficiency water-reducing agent is a β-naphthalenesulfonic acid formaldehyde condensate, with a solid content of 20%-40%. The water-cement ratio of the matrix slurry is 0.25-0.35, and the total amount of cementitious material is 700-900 kg / m³.
[0010] Preferably, in step three, during the composite mixing process of the fiber and the matrix, the internal temperature of the mixer is controlled at 15-30℃ through a cooling water circulation system.
[0011] Preferably, in step three, after the fiber and matrix are mixed, 0.1%-0.5% of the total mass of the unreinforced ultra-tough concrete is added to the mixture. The polyacrylonitrile fiber has a length of 3-6 mm and a diameter of 8-15 μm. The mixture is then stirred for 1-2 minutes at a speed of 300-500 rpm to ensure that the polyacrylonitrile fiber is evenly distributed in the mixture.
[0012] Preferably, in step four, the inner wall of the mold is pre-coated with a release agent, which is an aqueous paraffin emulsion with a solid content of 30%-50% and a coating amount of 20-50 g / m². During the compression molding process, the pressure is applied in two stages. The first stage applies a pressure of 0.2-0.5 MPa and holds the pressure for 5-10 seconds. The second stage applies a pressure of 0.5-2 MPa and holds the pressure for 10-30 seconds. The interval between the two stages of pressure is 2-5 seconds.
[0013] Preferably, in step four, before compression molding, a layer of fine sand with a thickness of 2-5 mm is laid at the bottom of the mold, the particle size of the fine sand is 0.3-0.6 mm, and the laying density of the fine sand layer is 1.5-2.0 kg / m². After molding, an anti-slip pattern with a depth of 1-3mm is formed on the upper surface of the cover plate by an embossing process. The anti-slip pattern is in the shape of a rhombus with a side length of 10-20mm and a spacing of 5-10mm between adjacent rhombuses.
[0014] Preferably, in step five, the heating rate inside the steam curing chamber is 10-20℃ / h, the cooling rate is 15-25℃ / h, and the relative humidity inside the chamber is maintained at ≥90% by the steam generator during the steam curing process; During natural curing, cover the surface of the cover with a polyethylene moisture-retaining film and spray water 2-3 times a day, with each spray amount being 100-200mL / m².
[0015] Preferably, in step five, after the integrated curing is completed, the cover plate is placed in a hot air drying oven at a temperature of 40-60℃ for 2-4 hours and the hot air velocity is 1-3m / s. After drying, a layer of silicone waterproofing agent is sprayed onto the surface of the cover plate. The silicone waterproofing agent is a sodium methylsilicate solution with a concentration of 10%-20% and a spraying amount of 100-200g / m². After spraying, it is allowed to dry naturally for 12-24 hours.
[0016] Compared with the prior art, the present invention provides a method for integral molding of high-toughness fiber-reinforced concrete, which has the following beneficial effects: 1. In this invention, by mixing polyvinyl alcohol fiber and basalt fiber at a specific mass ratio and adding cellulose ether dispersant for dry mixing, a mixed fiber mixture is obtained, which improves the uniformity of fiber dispersion in the concrete matrix; during the composite mixing process of fiber and matrix, the temperature is controlled by a cooling water circulation system, and polyacrylonitrile fiber is added to enhance the bonding performance between fiber and matrix, thereby improving the overall toughness and crack resistance of the concrete cover plate.
[0017] 2. In this invention, vibration compaction is used in the molding stage, followed by pressure application for molding. The pressure is applied in two stages. After the first stage of low pressure holding, a certain time interval is given before the second stage of high pressure holding is applied, which helps to remove air bubbles and improve compactness. A fine sand layer is laid at the bottom of the mold and anti-slip patterns are imprinted on the upper surface, so that the cover plate has both good molding quality and anti-slip function.
[0018] 3. In this invention, through an integrated curing process, the cover plate blank is first placed in a high-temperature and high-humidity curing chamber with the mold, then heated and kept warm in a steam curing box and then cooled down. Finally, it is naturally cured indoors and covered with a moisturizing film and sprayed with water regularly, thus achieving full temperature and humidity control. Subsequently, it is dried with hot air and sprayed with an organosilicon waterproofing agent, which improves the density, impermeability and long-term durability of the cover plate. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1: A method for integral molding of high-toughness fiber-reinforced concrete, comprising the following steps: Step 1: Fiber dispersion pretreatment. Polyvinyl alcohol fibers with a length of 6 mm and basalt fibers with a length of 8 mm are mixed at a mass ratio of 1:0.5. 0.5% of the total fiber mass of cellulose ether dispersant is added. The mixture is dry-mixed in a mixer at a speed of 200 rpm for 3 minutes to obtain a mixed fiber mixture. Step 2: Preparation of matrix slurry. Cement, silica fume, quartz sand, naphthalene-based high-efficiency water-reducing agent and water are mixed at a mass ratio of 1:0.15:0.8:0.01:0.25 and stirred in a mixer at 600 rpm for 5 minutes to obtain a concrete matrix slurry with a fluidity of 180 mm. Step 3: Composite mixing of fiber and matrix. Slowly add the mixed fiber mixture to the concrete matrix slurry and continue mixing at 400 rpm for 3 minutes to obtain unreinforced ultra-tough concrete mixture. Step 4: Compression molding. The unreinforced ultra-tough concrete mixture is injected into the mold and vibrated to compact it for 2 minutes under the conditions of vibration frequency of 50Hz and amplitude of 0.5mm. Then, it is compression molded to obtain the cover plate blank. Step 5: Integrated curing. Place the cover plate blank along with the mold in a curing room with a temperature of 20℃ and a relative humidity of over 95% for 12 hours. After demolding, place the cover plate in a steam curing box with a temperature of 80℃ for 8 hours, and then transfer it to an indoor curing room with a temperature of 20℃ for 3 days to obtain a high-toughness fiber-reinforced concrete cover plate.
[0021] In step one, the diameter of the polyvinyl alcohol fiber is 10 μm, the diameter of the basalt fiber is 12 μm, and the total volume of polyvinyl alcohol fiber and basalt fiber in the mixed fiber mixture is 1.5% of the total volume of concrete.
[0022] In step one, before fiber dispersion pretreatment, polyvinyl alcohol fiber and basalt fiber are dried in an oven at 60°C for 1 hour. The dried fibers were premixed for 2 minutes in a mixer at 100 rpm, and then a cellulose ether dispersant, hydroxypropyl methylcellulose, was added for dry mixing.
[0023] In step two, the cement is 52.5 grade ordinary Portland cement with a specific surface area ≥350m² / kg; The silica fume has a SiO2 content of ≥92% and a specific surface area of ≥18000 m² / kg; The particle size range of quartz sand is 0.1-1.0 mm, of which 0.1-0.3 mm particles account for 30%, 0.3-0.6 mm particles account for 40%, and 0.6-1.0 mm particles account for 30%. The naphthalene-based high-efficiency water-reducing agent is a β-naphthalenesulfonic acid formaldehyde condensate with a solid content of 20%. The water-cement ratio of the matrix slurry is 0.25, and the total amount of cementitious material is 700 kg / m³.
[0024] In step three, during the composite mixing of the fiber and the matrix, the internal temperature of the mixer is controlled at 15℃ through a cooling water circulation system.
[0025] In step three, after the fiber and matrix are mixed, 0.1% of the total mass of polyacrylonitrile fiber is added to the unreinforced ultra-tough concrete mixture. The polyacrylonitrile fiber has a length of 3 mm and a diameter of 8 μm. The mixture is then stirred for 1 minute at a speed of 300 rpm to ensure that the polyacrylonitrile fiber is evenly distributed in the mixture.
[0026] In step four, the inner wall of the mold is pre-coated with a release agent, which is a water-based paraffin emulsion with a solid content of 30% and a coating amount of 20g / m². During the compression molding process, the pressure is applied in two stages. The first stage applies a pressure of 0.2 MPa and holds the pressure for 5 seconds. The second stage applies a pressure of 0.5 MPa and holds the pressure for 10 seconds. The interval between the two stages of pressure is 2 seconds.
[0027] In step four, before compression molding, a 2mm thick layer of fine sand is laid at the bottom of the mold. The particle size of the fine sand is 0.3mm and the density of the fine sand layer is 1.5kg / m². After molding, an anti-slip pattern with a depth of 1mm is formed on the upper surface of the cover plate by an embossing process. The anti-slip pattern is in the shape of a rhombus with a side length of 10mm and a spacing of 5mm between adjacent rhombuses.
[0028] In step five, the heating rate inside the steam curing chamber is 10℃ / h, the cooling rate is 15℃ / h, and the relative humidity inside the chamber is maintained at ≥90% by the steam generator during the steam curing process; During natural curing, the surface of the cover plate is covered with a polyethylene moisture-retaining film, and water is sprayed twice a day, with each spray amount being 100mL / m².
[0029] In step five, after the integrated curing is completed, the cover plate is placed in a hot air drying oven at 40℃ for 2 hours and the hot air velocity is 1m / s. After drying, a layer of silicone waterproofing agent is sprayed onto the surface of the cover plate. The silicone waterproofing agent is a sodium methylsilicate solution with a concentration of 10% and a spraying amount of 100g / m². After spraying, it is allowed to dry naturally for 12 hours.
[0030] Example 2: A method for integral molding of high-toughness fiber-reinforced concrete, comprising the following steps: Step 1: Fiber dispersion pretreatment. Polyvinyl alcohol fibers with a length of 9 mm and basalt fibers with a length of 12 mm are mixed at a mass ratio of 1:1.2. 1.2% of the total fiber mass of cellulose ether dispersant is added. The mixture is dry-mixed in a mixer at a speed of 300 rpm for 4 min to obtain a mixed fiber mixture. Step 2: Preparation of matrix slurry. Cement, silica fume, quartz sand, naphthalene-based high-efficiency water-reducing agent and water are mixed at a mass ratio of 1:0.22:1.2:0.02:0.30 and stirred in a mixer at 800 rpm for 8 minutes to obtain a concrete matrix slurry with a fluidity of 200 mm. Step 3: Composite mixing of fiber and matrix. Slowly add the mixed fiber mixture to the concrete matrix slurry and continue mixing at 500 rpm for 5 minutes to obtain unreinforced ultra-tough concrete mixture. Step 4: Compression molding. The unreinforced ultra-tough concrete mixture is injected into the mold and vibrated to compact it for 4 minutes under the conditions of vibration frequency of 75Hz and amplitude of 1.0mm. Then, it is compression molded to obtain the cover plate blank. Step 5: Integrated curing. Place the cover plate blank along with the mold in a curing room with a temperature of 25℃ and a relative humidity of over 95% for 18 hours. After demolding, place the cover plate in a steam curing box with a temperature of 88℃ for 12 hours, and then transfer it to an indoor curing room with a temperature of 23℃ for 5 days to obtain a high-toughness fiber-reinforced concrete cover plate.
[0031] In step one, the diameter of the polyvinyl alcohol fiber is 20 μm, the diameter of the basalt fiber is 16 μm, and the total volume of polyvinyl alcohol fiber and basalt fiber in the mixed fiber mixture is 2.5% of the total volume of concrete.
[0032] In step one, before fiber dispersion pretreatment, polyvinyl alcohol fiber and basalt fiber are dried in an oven at 70°C for 1.5 hours. The dried fibers were premixed in a mixer at 150 rpm for 2.5 min, and then a cellulose ether dispersant, hydroxypropyl methylcellulose, was added for dry mixing.
[0033] In step two, the cement is 52.5 grade ordinary Portland cement with a specific surface area ≥350m² / kg; The silica fume has a SiO2 content of ≥92% and a specific surface area of ≥18000 m² / kg; The particle size range of quartz sand is 0.1-1.0 mm, of which 0.1-0.3 mm particles account for 35%, 0.3-0.6 mm particles account for 45%, and 0.6-1.0 mm particles account for 20%. The naphthalene-based high-efficiency water-reducing agent is a β-naphthalenesulfonic acid formaldehyde condensate with a solid content of 30%. The water-cement ratio of the matrix slurry is 0.30, and the total amount of cementitious material is 800 kg / m³.
[0034] In step three, during the composite mixing of the fiber and the matrix, the internal temperature of the mixer is controlled at 22°C through a cooling water circulation system.
[0035] In step three, after the fiber and matrix are mixed, 0.3% of the total mass of polyacrylonitrile fiber is added to the unreinforced ultra-tough concrete mixture. The polyacrylonitrile fiber has a length of 4 mm and a diameter of 12 μm. The mixture is then stirred for 1.5 min at a speed of 400 rpm to ensure that the polyacrylonitrile fiber is evenly distributed in the mixture.
[0036] In step four, the inner wall of the mold is pre-coated with a release agent, which is a water-based paraffin emulsion with a solid content of 40% and a coating amount of 35g / m². During the compression molding process, the pressure is applied in two stages. The first stage applies a pressure of 0.3 MPa and holds the pressure for 7 seconds. The second stage applies a pressure of 1.2 MPa and holds the pressure for 20 seconds. The interval between the two stages of pressure is 3 seconds.
[0037] In step four, before compression molding, a 3mm thick layer of fine sand is laid at the bottom of the mold. The particle size of the fine sand is 0.4mm and the density of the fine sand layer is 1.7kg / m². After molding, an anti-slip pattern with a depth of 2mm is formed on the upper surface of the cover plate by an embossing process. The anti-slip pattern is in the shape of a rhombus with a side length of 15mm and a spacing of 7mm between adjacent rhombuses.
[0038] In step five, the heating rate inside the steam curing chamber is 15℃ / h, the cooling rate is 20℃ / h, and the relative humidity inside the chamber is maintained at ≥90% by the steam generator during the steam curing process. During natural curing, the surface of the cover plate is covered with a polyethylene moisture-retaining film, and water is sprayed twice a day, with each spray amount being 150mL / m².
[0039] In step five, after the integrated curing is completed, the cover plate is placed in a hot air drying oven at 50°C for 3 hours and the hot air velocity is 2m / s. After drying, a layer of silicone waterproofing agent is sprayed onto the surface of the cover plate. The silicone waterproofing agent is a sodium methylsilicate solution with a concentration of 15% and a spraying amount of 150g / m². After spraying, it is allowed to dry naturally for 18 hours.
[0040] Example 3: A method for integral molding of high-toughness fiber-reinforced concrete, comprising the following steps: Step 1: Fiber dispersion pretreatment. Polyvinyl alcohol fibers with a length of 12 mm and basalt fibers with a length of 15 mm are mixed at a mass ratio of 1:2. 2% of the total fiber mass of cellulose ether dispersant is added. The mixture is dry-mixed in a mixer at a speed of 400 rpm for 5 minutes to obtain a mixed fiber mixture. Step 2: Preparation of matrix slurry. Cement, silica fume, quartz sand, naphthalene-based high-efficiency water-reducing agent and water are mixed in a mass ratio of 1:0.3:1.5:0.03:0.35 and stirred in a mixer at 1000 rpm for 10 minutes to obtain a concrete matrix slurry with a fluidity of 220 mm. Step 3: Composite mixing of fiber and matrix. The mixed fiber mixture is slowly added to the concrete matrix slurry and stirred for 8 minutes at 600 rpm to obtain unreinforced ultra-tough concrete mixture. Step 4: Compression molding. The unreinforced ultra-tough concrete mixture is injected into the mold and vibrated to compact it for 5 minutes under the conditions of vibration frequency of 100Hz and amplitude of 1.5mm. Then, it is compression molded to obtain the cover plate blank. Step 5: Integrated curing. Place the cover plate blank along with the mold in a curing room with a temperature of 30℃ and a relative humidity of over 95% for 24 hours. After demolding, place the cover plate in a steam curing box with a temperature of 95℃ for 16 hours, and then transfer it to an indoor environment with a temperature of 25℃ for natural curing for 7 days to obtain a high-toughness fiber-reinforced concrete cover plate.
[0041] In step one, the diameter of the polyvinyl alcohol fiber is 30 μm, the diameter of the basalt fiber is 20 μm, and the total volume of polyvinyl alcohol fiber and basalt fiber in the mixed fiber mixture is 3.5% of the total volume of concrete.
[0042] In step one, before fiber dispersion pretreatment, polyvinyl alcohol fiber and basalt fiber are dried in an oven at 80°C for 2 hours. The dried fibers were premixed for 3 minutes in a mixer at 200 rpm, and then a cellulose ether dispersant, hydroxypropyl methylcellulose, was added for dry mixing.
[0043] In step two, the cement is 52.5 grade ordinary Portland cement with a specific surface area ≥350m² / kg; The silica fume has a SiO2 content of ≥92% and a specific surface area of ≥18000 m² / kg; The particle size range of quartz sand is 0.1-1.0 mm, of which 40% are 0.1-0.3 mm, 50% are 0.3-0.6 mm, and 10% are 0.6-1.0 mm. The naphthalene-based high-efficiency water-reducing agent is a β-naphthalenesulfonic acid formaldehyde condensate with a solid content of 40%. The water-cement ratio of the matrix slurry is 0.35, and the total amount of cementitious material is 900 kg / m³.
[0044] In step three, during the composite mixing of the fiber and the matrix, the internal temperature of the mixer is controlled at 30°C through a cooling water circulation system.
[0045] In step three, after the fiber and matrix are mixed, 0.5% of the total mass of polyacrylonitrile fiber is added to the unreinforced ultra-tough concrete mixture. The polyacrylonitrile fiber has a length of 6 mm and a diameter of 15 μm. The mixture is then stirred for 2 minutes at a speed of 500 rpm to ensure that the polyacrylonitrile fiber is evenly distributed in the mixture.
[0046] In step four, the inner wall of the mold is pre-coated with a release agent, which is a water-based paraffin emulsion with a solid content of 50% and a coating amount of 50g / m². During the compression molding process, the pressure is applied in two stages. The first stage applies a pressure of 0.5 MPa and holds the pressure for 10 seconds. The second stage applies a pressure of 2 MPa and holds the pressure for 30 seconds. The interval between the two stages of pressure is 5 seconds.
[0047] In step four, before compression molding, a 5mm thick layer of fine sand is laid at the bottom of the mold. The particle size of the fine sand is 0.6mm and the density of the fine sand layer is 2.0kg / m². After molding, an anti-slip pattern with a depth of 3mm is formed on the upper surface of the cover plate by an embossing process. The anti-slip pattern is in the shape of a rhombus with a side length of 20mm and a spacing of 10mm between adjacent rhombuses.
[0048] In step five, the heating rate inside the steam curing chamber is 20℃ / h, the cooling rate is 25℃ / h, and the relative humidity inside the chamber is maintained at ≥90% by the steam generator during the steam curing process; During natural curing, the cover surface is covered with a polyethylene moisture-retaining film and sprayed with water 3 times a day, with each spray amount being 200mL / m².
[0049] In step five, after the integrated curing is completed, the cover plate is placed in a hot air drying oven at 60℃ for 4 hours and the hot air velocity is 3m / s. After drying, a layer of silicone waterproofing agent is sprayed onto the surface of the cover plate. The silicone waterproofing agent is a sodium methylsilicate solution with a concentration of 20% and a spraying amount of 200g / m². After spraying, it is allowed to dry naturally for 24 hours.
[0050] Comparative Example 1: The difference between this comparative example and Example 1 is that no silica fume was added when preparing the matrix slurry in this comparative example.
[0051] Comparative Example 2 differs from Example 1 in that: no cellulose ether dispersant was added for fiber dispersion pretreatment in step one of this comparative example.
[0052] Comparative Example 3 differs from Example 1 in that: in step four, no pressure was applied during molding in this comparative example; only vibration was used for compaction.
[0053] Comparative Example 4 differs from Example 1 in that steam curing was not performed in step five of the integrated curing process; instead, natural curing was carried out only at room temperature.
[0054] The high-toughness fiber-reinforced concrete cover plates prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests. The test items and test methods are as follows: The flexural strength test was conducted using a universal testing machine with a loading rate of 0.5 mm / min and a span of 300 mm. The bending toughness test was conducted using the four-point bending method, and the bending toughness index of the specimen was calculated through the load-deflection curve. The compressive strength test was conducted using a universal testing machine with a loading rate of 2.4 kN / s. For the water absorption test, the sample was dried at 105°C to constant weight, then immersed in water at room temperature for 24 hours, removed and the surface moisture was wiped off, and the percentage increase in mass was calculated.
[0055] The test data of the high-toughness fiber-reinforced concrete cover plates prepared in Examples 1-3 and Comparative Examples 1-4 are recorded in Table 1 below: Table 1 - Performance Test Data of High-Toughness Fiber-Reinforced Concrete Cover Plates Example 1 12.5 5.2 68.3 1.8 Example 2 14.8 6.1 72.6 1.5 Example 3 13.6 5.8 70.1 1.6 Comparative Example 1 9.2 3.5 55.4 3.2 Comparative Example 2 10.1 4.0 62.1 2.5 Comparative Example 3 8.5 3.1 58.7 2.8 Comparative Example 4 11.3 4.5 65.2 2.1 By comparing and analyzing the data in the table, it can be seen that the high-toughness fiber-reinforced concrete cover plates prepared using the processes in Examples 1-3 have significantly better performance than those prepared using the processes in Comparative Examples 1-4. This indicates that the present invention improves the uniformity of fiber dispersion in the concrete matrix by mixing polyvinyl alcohol fibers and basalt fibers at a specific mass ratio and adding cellulose ether dispersant for dry mixing. Furthermore, the temperature is controlled by a cooling water circulation system during the fiber-matrix composite mixing process, and polyacrylonitrile fibers are added to enhance the bonding performance between the fibers and the matrix, thereby improving the overall toughness and crack resistance of the concrete cover plate. In the compression molding stage, vibration compaction is followed by pressure application, with pressure applied in two stages. The first stage involves holding the pressure at low pressure for a certain period before applying the second stage at high pressure, which helps to remove air bubbles and improve density. A fine sand layer is laid at the bottom of the mold, and anti-slip patterns are imprinted on the upper surface, giving the cover both good molding quality and anti-slip function. Through an integrated curing process, the cover blank is first placed in a high-temperature and high-humidity curing chamber with the mold, then heated and kept warm in a steam curing box before being cooled, and finally naturally cured indoors with a moisturizing film and periodic water spraying, achieving full temperature and humidity control. Afterwards, it is dried with hot air and sprayed with an organosilicon waterproofing agent, which improves the density, impermeability, and long-term durability of the cover.
[0056] By comparing and analyzing the relevant data in the table, it can be seen that the high-toughness fiber-reinforced concrete cover plate prepared by the molding process of the present invention has good mechanical properties, toughness and waterproofness.
[0057] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0058] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for integral molding of high-toughness fiber-reinforced concrete, characterized in that: Includes the following steps: Step 1: Fiber dispersion pretreatment. Polyvinyl alcohol fibers with a length of 6-12 mm and basalt fibers with a length of 8-15 mm are mixed at a mass ratio of 1:0.5 to 1:
2. 0.5%-2% of cellulose ether dispersant by the total mass of the fibers is added. The mixture is then dry-mixed in a mixer at a speed of 200-400 rpm for 3-5 minutes to obtain a mixed fiber mixture. Step 2: Preparation of matrix slurry. Cement, silica fume, quartz sand, naphthalene-based high-efficiency water-reducing agent and water are mixed at a mass ratio of 1:0.15-0.3:0.8-1.5:0.01-0.03:0.25-0.35 and stirred in a mixer at a speed of 600-1000 rpm for 5-10 minutes to obtain a concrete matrix slurry with a fluidity of 180-220 mm. Step 3: Composite mixing of fiber and matrix. Slowly add the mixed fiber mixture to the concrete matrix slurry and continue mixing at 400-600 rpm for 3-8 minutes to obtain unreinforced ultra-tough concrete mixture. Step 4: Compression molding. The unreinforced ultra-tough concrete mixture is injected into the mold and vibrated to compact it for 2-5 minutes under the conditions of vibration frequency of 50-100Hz and amplitude of 0.5-1.5mm. Then, it is compression molded to obtain the cover plate blank. Step 5: Integrated curing. Place the cover plate blank along with the mold in a curing room with a temperature of 20-30℃ and a relative humidity of over 95% for 12-24 hours. After demolding, place the cover plate in a steam curing chamber with a temperature of 80-95℃ for 8-16 hours, and then transfer it to an indoor environment with a temperature of 20-25℃ for natural curing for 3-7 days to obtain a high-toughness fiber-reinforced concrete cover plate.
2. The method for integrated molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step one, the diameter of the polyvinyl alcohol fiber is 10-30 μm, the diameter of the basalt fiber is 12-20 μm, and the total volume of polyvinyl alcohol fiber and basalt fiber in the mixed fiber mixture is 1.5%-3.5% of the total volume of concrete.
3. The method for integrated molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step one, before fiber dispersion pretreatment, polyvinyl alcohol fiber and basalt fiber are placed in an oven at a temperature of 60-80℃ for 1-2 hours for drying. The dried fibers are premixed in a mixer at 100-200 rpm for 2-3 minutes, and then a cellulose ether dispersant, hydroxypropyl methylcellulose, is added for dry mixing.
4. The method for integrated molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step two, the cement is 52.5 grade ordinary Portland cement with a specific surface area ≥350m² / kg; The silica fume has a SiO2 content of ≥92% and a specific surface area of ≥18000 m² / kg; The particle size range of quartz sand is 0.1-1.0 mm, of which 0.1-0.3 mm particles account for 30%-40%, 0.3-0.6 mm particles account for 40%-50%, and 0.6-1.0 mm particles account for 10%-30%. The naphthalene-based high-efficiency water-reducing agent is a β-naphthalenesulfonic acid formaldehyde condensate, with a solid content of 20%-40%. The water-cement ratio of the matrix slurry is 0.25-0.35, and the total amount of cementitious material is 700-900 kg / m³.
5. The method for integrated molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step three, during the composite mixing process of the fiber and the matrix, the internal temperature of the mixer is controlled at 15-30℃ through a cooling water circulation system.
6. The method for integral molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step three, after the fiber and matrix are mixed, 0.1%-0.5% of the total mass of the unreinforced ultra-tough concrete is added to the mixture. The polyacrylonitrile fiber has a length of 3-6 mm and a diameter of 8-15 μm. The mixture is then stirred for 1-2 minutes at a speed of 300-500 rpm to ensure that the polyacrylonitrile fiber is evenly distributed in the mixture.
7. The method for integrated molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step four, the inner wall of the mold is pre-coated with a release agent, which is a water-based paraffin emulsion with a solid content of 30%-50% and a coating amount of 20-50g / m². During the compression molding process, the pressure is applied in two stages. The first stage applies a pressure of 0.2-0.5 MPa and holds the pressure for 5-10 seconds. The second stage applies a pressure of 0.5-2 MPa and holds the pressure for 10-30 seconds. The interval between the two stages of pressure is 2-5 seconds.
8. The method for integral molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step four, before compression molding, a layer of fine sand with a thickness of 2-5mm is laid at the bottom of the mold. The particle size of the fine sand is 0.3-0.6mm, and the laying density of the fine sand layer is 1.5-2.0kg / m². After molding, an anti-slip pattern with a depth of 1-3mm is formed on the upper surface of the cover plate by an embossing process. The anti-slip pattern is in the shape of a rhombus, with a side length of 10-20mm and a spacing of 5-10mm between adjacent rhombuses.
9. The method for integral molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step five, the heating rate inside the steam curing chamber is 10-20℃ / h, the cooling rate is 15-25℃ / h, and the relative humidity inside the chamber is maintained at ≥90% by the steam generator during the steam curing process. During natural curing, cover the surface of the cover with a polyethylene moisture-retaining film and spray water 2-3 times a day, with each spray amount being 100-200mL / m².
10. The method for integral molding of high-toughness fiber-reinforced concrete according to claim 1, characterized in that: In step five, after the integrated curing is completed, the cover plate is placed in a hot air drying oven at a temperature of 40-60℃ for 2-4 hours and the hot air velocity is 1-3m / s. After drying, a layer of silicone waterproofing agent is sprayed onto the surface of the cover plate. The silicone waterproofing agent is a sodium methylsilicate solution with a concentration of 10%-20% and a spraying amount of 100-200g / m². After spraying, it is allowed to dry naturally for 12-24 hours.